3-Hydroxy-2-(3´-methyl-2´-thienyl)-4-oxo-4H-1-benzopyran as an Analytical Reagent for the Spectrophotometric Determination of Tungsten(VI) - Agnihotri, R.; Agnihotri, N.; Kamal, Raj; R. Mehta, Jaswant (Asian Journal of Chemistry, 2010)
An extractive spectrophotometric method is developed for the trace determination of tungsten. Tungsten(VI) forms a yellow (1:4) complex with 3-hydroxy-2-(3'-methyl-2'-thienyl)- 4-oxo-4H-1-benzopyran (HMTB) in perchloric acid medium. The coloured species is quantitatively extracted into dichloromethane and shows maximum absorbance at 415-423 nm. The method obeys Beer's law up to 3.6 μg W mL-1, having molar absorptivity, Sandell's sensitivity and correlation coefficient of 5.80 × 104 dm3 mol-1 cm-1, 0.0032 μg W cm-2 and 0.9963, respectively at 420 nm. The method is free from the interference of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Ta, Mo, U, Zr, Th, Ce, Se, Re, platinum metals and many other analytically important elements. The method has good reproducibility and can be satisfactorily applied to the determination of tungsten in several samples of varying complexity.